The Legal Status of the Location Determination Decree (Kpts. 548/IV/2023) in Land Acquisition within Forest Areas: A Case Study of the Pekanbaru Ring Road Toll Project - Frans Riady Johan Situmorang; Edy Sutrisno (Legalis : Journal of Law Review, 2026)
This study explores the intersection between land acquisition and forestry governance in Indonesia, focusing on its implications for the implementation of National Strategic Projects (PSN). The analysis identifies a regulatory misalignment arising from the lack of procedural and temporal coherence between the two regimes, particularly concerning the issuance of the Location Determination Decree (Penetapan Lokasi or Penlok) prior to the formal reclassification of forest areas. Such inconsistency has generated overlapping institutional mandates, uneven implementation, and legal uncertainty in project execution. Employing a qualitative juridical approach, this study relies on document analysis of key regulations and administrative records. Using the Pekanbaru Ring Road Toll Project as a case study, the findings demonstrate how policy acceleration may blur legal boundaries and affect the overall coherence of administrative governance. The study recommends refining Article 67(3) of Government Regulation No. 23 of 2021 on Forestry Management to align with Government Regulation No. 19 of 2021 on Land Procurement for Public Interest. This harmonization would strengthen legal certainty, institutional coordination, and governance integrity, thereby promoting a more legitimate and sustainable framework for infrastructure development.